Risk factors for absence of catch‐up growth in small for gestational age very low‐birthweight infants. Issue 9 (12th September 2019) - Arai, Sakiko; Sato, Yoshiaki; Muramatsu, Hideki; Yamamoto, Hidenori; Aoki, Fumiko; Okai, Yu; Kataoka, Shinsuke; Hanada, Yu; Hamada, Motoharu; Morimoto, Yoshihito; Kojima, Seiji; Natsume, Jun; et al.
Abstract: Background: Many small for gestational age (SGA) infants have catch‐up growth during the first 2 years of life, but approximately 10% have no catch‐up growth, and short stature continues into adulthood. Identification of risk factors for absence of catch‐up growth at an early age may be useful for earlier diagnosis and earlier treatment. Methods: This was a retrospective multicenter study. The subjects were SGA infants with very low‐birthweight (VLBW), who were followed up until the age of 3 years. The risk factors for absence of catch‐up growth were identified on statistical analysis. Results: Of the 217 SGA infants in this study, 181 were in the catch‐up group and 36 were in the no catch‐up group. The catch‐up rate was 83%. On multivariate analysis adjusted for gestational age, birthweight, birth height, and birth head circumference, multipara, Z and ΔZ scores of length at 12 months of corrected age, and the Z score of height at 24 months of corrected age were risk factors for lack of catch‐up at 3 years. Conclusions: The length Z and ΔZ scores at 12 months of corrected age may be useful for an earlier diagnosis and earlier initiation of growth hormone treatment in VLBW infants.